Predictors of the Quality of Life Among Parents/Caregivers with Children with Special Health Care Needs (CSHCN) - Macabago, Jinky M. (Technium Social Sciences Journal, 2021)
This study investigates the predictors of the quality of life of parents/caregivers who have children with special health care needs (CSHCNs). One hundred and seven parents/caregivers with CSHCN were asked to answer a paper and pen questionnaire on profile about themselves and their child with special health care needs. Also, they answered a WHO quality of life questionnaire and the multidimensional scale of perceived social support. When all the independent variables (perceived social support from significant other, family, friends, income, gender of the parent/caregiver, and presence of intervention) were entered into the regression equation, the model yielded a significant result, F=7.44 at p<.01 and it contributes 26.7% to the variance of quality of life. But, only two variables out of six-the perceived social support from the significant other and income-are the significant predictors to quality of life, with B=0.34, t=2.62, p<.01 and B=0.311, t=3.48, p<.01.